Optimization of Renewable Energy Systems for Remote Areas in Indonesia Using Hybrid PV-Wind-Battery Systems - Dzulfikar Al Faruq; Salsabila Putri Pambudhi; Ahmad Ridhwan Firdausi (Proceeding of the International Conferences on Engineering Sciences, 2025)
This paper presents an optimization approach for a hybrid photovoltaic (PV)-wind-battery energy system tailored for remote areas in Indonesia. Due to the archipelagic nature of the country, many remote areas lack access to the national power grid, making renewable energy solutions crucial. This study utilizes a genetic algorithm to optimize system configurations, balancing energy production, storage requirements, and cost efficiency. Results indicate that the proposed hybrid system can meet local demand with high reliability and at lower costs compared to diesel generators. The study also addresses environmental and social impacts, proposing sustainable energy strategies for Indonesia's underserved regions.